A study on the metabolic outcome of patients who underwent bariatric surgery in Hospital Universiti Sains Malaysia - Abidin, Muhd Abdul Ghani Zenol (2020)
Background: Hospital Universiti Sains Malaysia is the only centre in East Coast of Malaysia who offered bariatrics surgery services since October 2016. Bariatric surgery confers benefits to obese in terms of weight, blood pressure reduction and normalisation of blood sugars. However, the information on the effect of bariatric surgery in this centre is lacking. Methods: This retrospective study involving review of medical records of all patients underwent sleeve gastrectomy or Roux-en-Y gastric bypass in Hospital Universiti Sains Malaysia between October 2016 until July 2019. We analyse weight, blood pressure and biochemical parameters at baseline and 6 months post-surgery using student paired t-test. McNemar test is used to determine change in oral hypoglycaemic agents and/or total insulin dose, total number of anti-hypertensives and total number of anti-lipids. Result: A total of 39 patients were analysed. Mean weight reduction was 29.14 (95% CI = 24.75, 33.53) kg, SBP mean reduction was 17.87 (95% CI = 11.17, 24.58) mmHg and DBP mean reduction was 7.18 (95% CI = 3.21, 11.15) mmHg. Mean HbA1c reduction was 3.13 (95% CI = 2.07, 4.19) %, triglycerides mean reduction of 0.29 (95% CI = 0.12, 0.47) mmol/L. At 6 months post-surgery, 16 participants (61%) had remission in hypertension, 41% had reduction in number of antihypertensive. Eight patients (40%) had remission of diabetes and 4 patients (20%) who were diabetics becoming pre-diabetes. Only 4 patients were on oral hypoglycaemic agents and/or 3 patients were able to off insulin. Total insulin dose were markedly reduced, with median dose of 148 (34) iu to 24 (34) post-operatively. Five patients (25%) had normalisation of lipid profile and were able to off anti-lipids. Conclusion: Bariatric surgery among our patients with obesity confers significant metabolic benefits which is comparable to other centres.